A Study On (K, Na) NbO3 Thin Films With Optimized Layer: Effect On Physical And Electrical Properties - Nurul Azuwa, Azmi; Umar Al-Amani, Azlan; Maziati Akmal, Mohd Hatta; Mohd Asyadi ‘Azam, Mohd Abid; Mohd Warikh, Abd Rashid (Trans Tech Publications, 2016)
(K, Na)NbO3 (KNN) thin films were prepared by sol-gel technique. Spin coating deposition and rapid thermal annealing (RTP) process were applied to produce the KNN thin films. The films obtained demonstrated that highly crystallographic orientation was produced at five layer deposition with increase (preferred orientation) peak at (1 1 1). The thickness of five layers thin films observed by field emission scanning electron microscopy (FE-SEM) was determined to be ~200nm. However, the inhomogeneous distribution of KNN particles was detected in KNN thin films. The distribution of KNN elements was confirmed by energy-dispersive X-ray (EDX) spectra. Improvement was observed in resistivity (2.71-7.81×106 W.cm) and dielectric loss (0.35%-0.21%) following the increasing number of layers.